Astrazeneca equity research - adapting to a dynamic pharmaceutical sector as a key to success - Papp, Alexander (2022)
This master thesis analyzes AstraZeneca’s business model as well as competitive positioning in a dynamic pharmaceutical sector and provides an in-depth analysis of the company’s financial performance. By analyzing the firm’s strategy and core strengths and weaknesses compared to its competition, we are able to forecast its future performance. The goal of this thesis is to derive the fair value of AstraZeneca in the context of a transforming pharmaceutical business model.